2015
DOI: 10.1121/1.4935135
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic property reconstruction of a pygmy sperm whale (Kogia breviceps) forehead based on computed tomography imaging

Abstract: Computed tomography (CT) imaging and sound experimental measurements were used to reconstruct the acoustic properties (density, velocity, and impedance) of the forehead tissues of a deceased pygmy sperm whale (Kogia breviceps). The forehead was segmented along the body axis and sectioned into cross section slices, which were further cut into sample pieces for measurements. Hounsfield units (HUs) of the corresponding measured pieces were obtained from CT scans, and regression analyses were conducted to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…; Goold and Clarke ; Song et al. ; Thornton et al. suggest acoustic specializations linked to this unusual structure, but some of the unique cranial and soft tissue structures of the head of Physeter may be derived for ramming behaviors (Panagiotopoulou et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Goold and Clarke ; Song et al. ; Thornton et al. suggest acoustic specializations linked to this unusual structure, but some of the unique cranial and soft tissue structures of the head of Physeter may be derived for ramming behaviors (Panagiotopoulou et al.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the bony anatomy, physeteroids also are the only living odontocetes to lack a melon, instead possessing a spermaceti organ, and uniquely retain distinct left and right nasal tracks that lead to a single blowhole (Cranford 1999;Heyning 1989). Studies of the roles of skull and soft tissues of Physeter (Huggenberger et al 2014;Song et al 2017) and Kogia (Karol et al 1978;Goold and Clarke 2000;Song et al 2015;Thornton et al 2015 suggest acoustic specializations linked to this unusual structure, but some of the unique cranial and soft tissue structures of the head of Physeter may be derived for ramming behaviors (Panagiotopoulou et al 2016;Alam et al 2016) as well. The bizarre cranial morphology described above has resulted in Kogia having a significant influence on the identification of major sources of variation in our facial morphology dataset; Kogia forms an extreme outlier for PC 4 of the whole skull dataset and principle components 3, 4, and 6 for the half skull dataset.…”
Section: Evolution Of the Odontocete Skullmentioning
confidence: 99%
“…These hypotheses were supported in part by a subsequent study by Song et al, through the reconstruction of the acoustic property distributions of a pygmy sperm whale forehead. 27 The results suggested that the sounds generated at the phonic lips would propagate into the spermaceti organ. These sounds would likely be reflected by air-filled structures, soft tissues, and the skull before forming sound beams.…”
mentioning
confidence: 97%
“…Pygmy sperm whale beam formation studies could deepen our understanding of its biosonar system. Although the sound propagation of this species has been proposed and discussed in previous studies by interpreting the species' lipid topography and morphology, [24][25][26][27] no direct study has been conducted to verify the proposals. The sounds produced at the source were proposed to be divided into two parts.…”
mentioning
confidence: 99%
See 1 more Smart Citation